Public administration in the field of physical culture and sports: theoretical principles and approaches to definition - Morhunov, O. A.; Моргунов, О. А.; ORCID: http://orcid.org/0000-0003-2259-3620 (Підприємництво, господарство і право. – 2021. – № 12. – С. 76-82, 2021)
Метою статті є аналіз та узагальнення наукових підходів до визначення категорії «публічне адміністрування у сфері фізичної культури і спорту», що містяться у вітчизняній та іноземній науковій літературі, а також надання авторського формулювання цього поняття та його складників.

Abstract. The purpose of the article is to analyse and generalise scientific approaches to defining the category of “public administration in the field of physical culture and sports” contained in domestic and foreign scientific literature, as well as to formulate an original author’s perspective on its concepts and components. Results. The article studies theoretical approaches to defining the essence and features of public administration in the field of physical culture and sports. The focus is on public administration through making public policy on physical culture and sports. It is emphasised that the formation of the principles of public administration of physical culture and sports in this regard should take into account the concept of good governance. The author underlines the section of the European Charter of Local Self-Government, which defines a number of principles of local self-government, including: 1) the free resolution of issues not excluded from the scope of competence; 2) protection of territorial borders of local self-government bodies, determination of own internal administrative structures; 3) free performance of functions by local elected representatives; 4) administrative supervision of local self-government bodies only in the manner and in cases provided by the constitution or law; 5) own adequate financial resources, which they can freely dispose of within their powers; 6) cooperation and creation of consortia with other local governments to perform tasks of common interest; 7) use of legal remedies to ensure the free exercise of their powers. It should be noted that the European Charter of Local Self-Government defines the protection and strengthening of local self-government in various European countries as an important contribution to the development of Europe on the principles of democracy and decentralisation. Conclusions. It is concluded that the leading role of the state in the development of sports and physical culture is immutable and relevant today. However, no less important for the modern development of physical culture and sports is the understanding of the different legal status of the participants in the relevant legal relations, including not only state and local governments, but also civil society institutions. Their role in the development of these fields cannot be underestimated. It should be understood that only the interaction of all actors of legal relations contributes to the development of physical culture and sports.

Целью статьи является анализ и обобщение научных подходов к определению категории «публичное администрирование в сфере физической культуры и спорта», содержащихся в отечественной и иностранной научной литературе, а также предоставление авторской формулировки этого понятия и его составляющих.
Публічне адміністрування у сфері фізичної культури і спорту: теоретичні засади та підходи до визначення
Morhunov, O. Public administration in the field of physical culture and sports: theoretical principles and approaches to definition / Oleksandr Morhunov // Підприємництво, господарство і право. – 2021. – № 12. – С. 76-82. – DOI: https://doi.org/10.32849/2663-5313/2021.12.13.
Morhunov, Oleksandr (2021). Public administration in the field of physical culture and sports: theoretical principles and approaches to definition. Entrepreneurship, Economy and Law , 12, 76–82, doi https://doi.org/10.32849/2663-5313/2021.12.13.
Keywords: Державне адміністративне управління. Адміністративна діяльність. State Administration. Administrative Activity. Государственное административное управление. Административная деятельность; Адміністративне право та процес. Administrative Law and Procedure. Административное право и процесс; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; фізична культура; спорт; публічне адміністрування; физическая культура; публичное администрирование; physical culture; sports; public administration